Wish and care method: empowering women for breast cancer screening - Nursanti, Wigi Anis; Setiyawati, Nanik; Wahyuningsih, Heni Puji (Intelektual Pustaka Media Utama, 2025)
Breast cancer ranks as the most prevalent type of cancer and the fifth leading cause of death globally. Conducting early detection through breast self-examination (BSE) is a crucial preventive measure. The rate of early detection of breast cancer remains low due to insufficient knowledge and information, so health education is needed to increase BSE knowledge and information. There is a need for health education initiatives to enhance awareness, attitudes, and behavior related to BSE. One effective method of health education is the “wish and care” approach. This study aims to assess the impact of the wish and care method on knowledge, attitudes, and behavior. The study employed a quasi-experimental design with a pre-test-post-test two-group design. Data collection took place in 2023. The sample consisted of 60 women aged 30-50 years, who were divided into an experimental group receiving the wish and care method and a control group receiving conventional lectures. The results indicate an increase in knowledge, attitudes, and behavior both before and after the intervention in both the experimental and control groups. The wish and care method has more influence on BSE behavior. This study concludes that the wish and care method influence BSE knowledge, attitudes, and behavior.